The Debate about Qualitative Aspects of Social Science Research in the Academic Process in Nepal - Gautam, Sahadev (Far Western Review, 2024)
Research is a prerequisite to pursue an academic degree in social science (or any other discipline). Research is one of the intended outcomes of a dedication to an academically guided methodology. Students are required by the institution to submit their research in order to continue their academic career. This article explores concepts and practices in social research, seeking knowledge through secondary data and the researcher’s own experiences. In order to study critical points of view, the author gathered relevant literature. Research can take numerous forms, including articles, publications, theses, reports, and dissertations. The interpretation suggests that creativity and discovery serve as critical social cornerstones for modern academic transitions. This work investigates early circumstances in research from a social science perspective to evaluate the quality of academic research. Rather than being impartial, social research relies on human interpretation. Imagination and hypothesis are collaborative ways of generating new ideas based on gaps, but they do not constitute a research process. However, they guide the path for research in social sciences. Only research that improves awareness of damaging beliefs and one’s own societal responsibilities can generate new ideas in social situations.